Data Analysis of Bulacan State University Faculty Scientific Publication Based on Google Scholar using Web Data Scraping Technique - Victoriano, Jayson M.; Pulumbarit, Jaime P.; Lacatan, Luisito L.; Salivio, Richard Albert S.; Barawid, Rica Louise A. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – The paper aims to analyze and monitor the research publication productivity of the faculty members of Bulacan State University. This paper compiles all the scientific publications from Bulacan State University (BulSU) and its external campuses as an index in Google Scholar. This study was intended to track and monitor the scientific productivity of the faculty members of Bulacan State University and each college and campus. Method – With the use of web data scraping techniques, metadata files were gathered from various faculty research engagement in Google Scholar Database. Web scraping is the process of extracting useful information from web pages (HTML pages) and saving it in a format that you specify, such as Excel (.xls), CSV (comma-separated values), or any other structured format using PurseHub. Different stages of data extraction are completed before descriptive insight is provided to the university. The researchers used the web data scraping techniques to extract the necessary data in the web through the Google Scholar database to specifically gather the research outputs of the faculty members of Bulacan State University. Results – Results have shown that a significant increase that happened throughout the covered years on the number of publications was made possible by the scholarships and study breaks that the faculty members were able to get and a significant increase in the number of citations was brought by the benefits of collaborating with other researchers from other HEIs. Conclusion – Bulacan State University has seen both big improvements and stagnation with the growth of the number of publications being produced by the faculty members. Based on the results of the study, the publications of BulSU have experienced a significant increase due to the impact of scholarship and the benefits that comes with it to the productivity of the faculty members. On the other hand, the factor that affected the significant increase in citations is the collaborators with researchers from other academic institutions. Recommendation – The administration should consider doing necessary steps to encourage the faculty members who engage in research activities to create Google Scholar accounts for easy monitoring of publications and citations. This would allow the easier navigation of the research studies produced by the faculty members which will help the university monitor the progress of research activity effectively and for an impressive research activity, the researchers also recommend that the administration should also provide competitive incentives and positive reinforcements. The faculty, on the other hand, are recommended to broaden their horizon and engage in collaborations with other researchers from other academic institutions for wider perspective of things. Practical Implication – Maximizing the use of data scraping in gathering information about research activity from vast networks will make the navigation and organization of research activity easier. With this, monitoring the progress of faculty research productivity will also be done in ease.